Recognizing synesthesia on the international stage: The first scientific symposium on synesthesia (at The International Conference of Physiological Psychology, Paris, 1889). Issue 4 (1st October 2020) - Jewanski, Jörg; Simner, Julia; Day, Sean A.; Rothen, Nicolas; Ward, Jamie
ABSTRACT: At the first ever worldwide international conference of psychology in Paris, 1889, one symposium included a round-table event devoted entirely to the neurodevelopmental condition of synesthesia. Details of this seminal gathering on synesthesia and its international reception have been lost to historical obscurity. A synesthesia study committee emerged from this meeting, as well as a new research tool. Moreover, the scientific findings discussed during this symposium would be echoed over a hundred years later, when a new wave of synesthesia research in the late-twentieth century arose. This article sheds new light on this seminal gathering and aims to answer the following historical questions: Why was synesthesia included in this conference? What science was discussed? Who were the members of the committee and how did they come to be involved? What were their contributions to synesthesia research before, during, and after the conference? What has history shown us about the impact of this symposium on the science of synesthesia?